2020
DOI: 10.4018/ijebr.2020070103
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Relationship Among Service Quality of E-Commerce Websites, Customer Satisfaction, and Purchase Intention

Abstract: The purpose of this study is to analyze the impact of online service quality of e-commerce websites on customer satisfaction and purchase intention. The study identifies the dimensions of e-service quality on the basis of the literature review, which are website design, reliability, responsiveness, trust, and personalization. A survey of 278 avid users of three popular websites was taken to validate the model. The reliability and validity of the questionnaire were checked through the measurement model and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 58 publications
3
62
1
8
Order By: Relevance
“…The results of the analysis in this study indicate that the sixth hypothesis is supported, so it is evident that the better consumer satisfaction, the more consumers buy interest in online shopping platforms. These results are supported by several previous studies by Tandon et al, (2020;Cuong, 2020;Dash et al, 2021;Khatoon et al, 2020;Dhingra et al, 2020). Although there are contradictory findings by Hutchinson (2009;Permana et al 2020) who found that satisfaction had no significant effect on purchase intention.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The results of the analysis in this study indicate that the sixth hypothesis is supported, so it is evident that the better consumer satisfaction, the more consumers buy interest in online shopping platforms. These results are supported by several previous studies by Tandon et al, (2020;Cuong, 2020;Dash et al, 2021;Khatoon et al, 2020;Dhingra et al, 2020). Although there are contradictory findings by Hutchinson (2009;Permana et al 2020) who found that satisfaction had no significant effect on purchase intention.…”
Section: Discussionsupporting
confidence: 84%
“…Every company wants its customers to feel satisfied with both the products and services offered. This is because with consumer satisfaction, people's purchase intention is increasing (Tandon et al, 2020;Cuong, 2020;Dash et al, 2021;Khatoon et al, 2020;Dhingra et al, 2020). Although there are contradictory findings by Hutchinson (2009;Permana et al 2020) who found that satisfaction had no significant effect on purchase intention.…”
Section: Consumer Satisfaction and Purchase Intentionmentioning
confidence: 97%
See 2 more Smart Citations
“…Website can provoke customer engagement [56], purchase intentions [57], and generate satisfaction [58] toward product or service offering so that the website is suitable as a marketing media [18], where in this study, the website was used as an advertising media as well as publicity and public relations. Email can also generate customer engagement.…”
Section: Customer Can Comment and Respond To Our Posting Of Activities Thus Creates Bonding With Us I Like To Use These Two To Market Thementioning
confidence: 99%